Intestinal microbiota: a new perspective on delaying aging? - Zhang, Yuemeng; Wang, Xiaomei; Li, Wujuan; Yang, Yi; Wu, Zhuoxuan; Lyu, Yuhong; Yue, Changwu (Frontiers in Microbiology, 2023)
The global aging situation is severe, and the medical pressures associated with aging issues should not be underestimated. The need and feasibility of studying aging and intervening in aging have been confirmed. Aging is a complex natural physiological progression, which involves the irreversible deterioration of body cells, tissues, and organs with age, leading to enhanced risk of disease and ultimately death. The intestinal microbiota has a significant role in sustaining host dynamic balance, and the study of bidirectional communication networks such as the brain-gut axis provides important directions for human disease research. Moreover, the intestinal microbiota is intimately linked to aging. This review describes the intestinal microbiota changes in human aging and analyzes the causal controversy between gut microbiota changes and aging, which are believed to be mutually causal, mutually reinforcing, and inextricably linked. Finally, from an anti-aging perspective, this study summarizes how to achieve delayed aging by targeting the intestinal microbiota. Accordingly, the study aims to provide guidance for further research on the intestinal microbiota and aging.